Genetic association and functional implications of TLR4 rs1927914 polymorphism on colon cancer risk - Ang Li; Hui Gao; Hongjiao Wu; Yuning Xie; Zhenxian Jia; Zhenbang Yang; Zhi Zhang; Xuemei Zhang (BMC Cancer, 2024)
Abstract Background Colon cancer remains a major health concern worldwide, with genetic factors playing a crucial role in its development. Toll-like receptors (TLRs) has been implicated in various cancers, but their role in colon cancer is not well understood. This study aims to identify functional polymorphisms in the promoter and 3′UTR regions of TLRs and evaluate their association with colon cancer susceptibility. Methods We conducted a case-control study involving 410 colon cancer patients and 410 healthy controls from the Chinese population. Genotyping of polymorphisms in TLR3, TLR4, TLR5 and TLR7 was performed using PCR-RFLP and TaqMan MGB probes. Using logistic regression analysis, we evaluated the association of TLRs polymorphisms and the susceptibility to colon cancer. To understand the biological implications of the TLR4 rs1927914 polymorphism, we conducted functional assays, including luciferase reporter assay and electrophoretic mobility shift assay (EMSA). Results Our results demonstrated that the G-allele of the TLR4 rs1927914 polymorphism is significantly associated with a decreased risk of colon cancer (OR = 0.68, 95%CI = 0.50–0.91). Stratified analysis showed that TLR4 rs1927914 AG or GG genotype contributed to a decreased risk of colon cancer among younger individuals (OR = 0.52, 95%CI = 0.34–0.81), males (OR = 0.58, 95%CI = 0.38–0.87), non-smokers (OR = 0.58, 95%CI = 0.41–0.83) and non-drinker with OR (95%CI) of 0.66 (0.46–0.93). Functional assays demonstrated that in HCT116 and LOVO colon cancer cells, the luciferase activity driven by the TLR4 promoter with the rs1927914A allele was 5.43 and 2.07 times higher, respectively, compared to that driven by the promoter containing the rs1927914G allele. Electrophoretic mobility shift assay (EMSA) results indicated that the rs1927914G allele enhanced transcription factor binding. Using the transcription factor prediction tool, we found that the G allele facilitates binding of the repressive transcription factor Oct1, while the A allele does not. Conclusion The TLR4 rs1927914 polymorphism influence the susceptibility to colon cancer, with the G allele offering a protective effect through modulation of gene expression. These insights enhance our understanding of the genetic determinants of colon cancer risk and highlight TLR4 as a promising target for cancer prevention strategies.